Boston Paper - Systems of Mining in Large Bodies of Soft Ore - Richard Rothwell (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1888)
At the last meeting of the Institute, Mr. Per Larsson read a very interesting paper on the Chapin mine of Michigan, in which he described the systems of mining that had, at different times, been tried in that great ore-body, and especially the system now in use, which consists in working the ore out from the bottom upward in lifts. Shortly after that paper was written, but before it had been published, or that I had had an opportunity of reading it, I bad the pleasure of visiting the mine. At that time I was making a profes sional examination of a nnmber of the mines on theGogebic Range, and others in the Menominee region, Michigan and Wisconsin, and had occasion then, as during several previous visits, to study closely the methods and cost of mining in these districts. As the outcome of these investigations, it appeared evident to me that the system of working on the chamber-and-pillar plan, which up to that time had been the only method of underground work adopted in the Gogebic